1997
DOI: 10.1074/jbc.272.52.32773
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Inactivates NADPH Oxidase in Pig Neutrophils by Inhibiting Its Assembling Process

Abstract: Nitric oxide (NO) is now recognized as one of the key mediators in many physiological and pathological processes (see reviews in Refs. 1 and 2). NO is also known to be a multifunctional molecule, one function of which is to inactivate biologically important enzymes such as mitochondrial respiratory enzymes and GAPDH, which play important roles in energy production (3, 4), ribonucleotide reductase, which is the key enzyme for protein synthesis (5), and the superoxide-generating enzymes, NADPH oxidase (6) and xa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
79
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(90 citation statements)
references
References 32 publications
(21 reference statements)
11
79
0
Order By: Relevance
“…Nitric oxide is capable of inhibiting neutrophil superoxide anion production via a direct action on the membrane components of NADPH oxidase and the assembly of NADH/NADPH oxidase subunits [25]. However, NO has been considered to be a double-edged sword [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide is capable of inhibiting neutrophil superoxide anion production via a direct action on the membrane components of NADPH oxidase and the assembly of NADH/NADPH oxidase subunits [25]. However, NO has been considered to be a double-edged sword [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils have also been coupled commonly with inflammatory conditions, which are mostly associated with the accumulation of NO and its metabolites. Various reports demonstrated NOmediated biphasic regulation (14,16,17), stimulation (15,22), and even inhibition (18,20) of PMNs reactive species formation. These outcomes could be due to the differences in probes used to detect ROS/RNS, which exhibit different reactivity, specificity, and selectivity, and some probes even interact with NO (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from this laboratory as well as from others have demonstrated a biphasic role of NO on the reactive species formation in PMNs in response to arachidonic acid, fMLP, and PMA stimulation (14)(15)(16)(17). Low concentrations (10-100 nM) of NO potentiated reactive species generation by augmented ADP-ribosylation, intracellular calcium, and activation of ERK MAPK pathway, but higher concentrations (1 lM-1 mM) attenuated ROS generation through feed back inhibition of NADPH-oxidase and superoxide scavenging effect and activation of the guanylate cyclase-cyclic GMP pathway from the rat and human PMNs (15,16,(18)(19)(20). Indeed, NO suppressed NADPH oxidase-dependent superoxide production by S-nitrosylation of p47 subunit in human endothelial cells (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other proven or likely targets for nitrosylation in the NF-B pathway include the epidermal growth factor and src tyrosine kinases (24,25), which activate NF-B through p21 ras ; tyrosine phosphatases (26); and NADPH oxidase (27), known to activate NF-B through IKK (presumably by means of the oxidative inactivation of phosphatase). Given the multiple loci of S-nitrosylation in NF-Brelated pathways, the effects of S-nitrosylation may be considered analogous to those of phosphorylation, with a large number of regulatory permutations that combine ultimately to optimize cellular responses.…”
Section: Multifaceted Regulation Of Nf-b By S-nitrosylationmentioning
confidence: 99%